A multiplex real-time PCR method for the quantification of beef and pork fractions in minced meat. (15th February 2015) - Iwobi, A.; Sebah, D.; Kraemer, I.; Losher, C.; Fischer, G.; Busch, U.; Huber, I.
Highlights: We present a triplex real-time PCR method for the quantification of beef and pork. Limit of detection (LOD) of the method was 20 genome equivalents. Validation of assay on commercial meat products generated good results. Abstract: One popular staple food in many lands is minced meat, traditionally prepared from beef and/or pork fractions. While beef is the more expensive of the two meat fractions, the possibility exists for manufacturers to fraudulently declare higher proportions of it. Additionally, the need exists to protect consumers who, out of medical or ethical reasons, reject specific meat fractions. In this work, we report on a quantitative triplex real-time PCR approach for the quantification of meat in minced meat products. With the method, beef and pork fractions are quantified employing primer and probe sequences that specifically recognise cow and pig components, against the backdrop of myostatin, a universal sequence commonly found in mammals and poultry species. The limit of detection of the qPCR method was 20 genome equivalents, while the measurement of uncertainty was determined at 1.83%. The method was validated on several commercially available minced meat products and performed well in terms of handling, reproducibility and robustness.